Maintenance strategy selection using AHP and COPRAS under fuzzy environment - Fouladgar, Mohammad Majid; Yazdani-Chamzini, Abdolreza; Lashgari, Ali; Zavadskas, Edmundas Kazimieras; Turskis, Zenonas (International Journal of Strategic Property Management, 2012)
Asset management, as a systematic process of operating, maintaining, and upgrading physical assets, is an important element of decision-making in heavy equipment management and operation. Maintenance strategy selection plays a significant role in mining design. However, the nature of maintenance strategy selection is a complex multi-criteria decision making (MCDM) problem including both tangible and intangible parameters which are often in conflicting with each other. As well as when decision makers are uncertain in determining and defining the ratings and the weights of alternatives and criteria respectively, fuzzy theory provides an appropriate tool to handle the existing uncertainties. In this paper, a new fuzzy MCDM method based on the concepts of COPRAS (COmplex PRoportional ASsessment) and AHP (Analytical Hierarchy Process) was proposed to evaluate the feasible maintenance strategy. The linguistic terms are employed to assess the ratings and weights. Fuzzy AHP is utilized to calculate the weights of the evaluation criteria; then, the rankings of alternatives are computed based on fuzzy sets theory and COPRAS. A real world case study is presented to illustrate a potential application of the proposed model. First Publish Online: 12 Apr 2012